2004
DOI: 10.1590/s0037-86822004000300003
|View full text |Cite
|
Sign up to set email alerts
|

Doenças sexualmente transmissíveis na adolescência: estudo de fatores de risco

Abstract: RESUMO As doenças sexualmente transmissíveis são prevalentes na adolescência e facilitadoras da contaminação pelo HIV. A baixa idade das primeiras relações sexuais, a variabilidade de parceiros, o não uso de preservativo e o uso de drogas

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
14
1
24

Year Published

2005
2005
2017
2017

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 53 publications
(40 citation statements)
references
References 15 publications
1
14
1
24
Order By: Relevance
“…Such aspects are related to healthy behaviors, including sexual behaviors and protection. At the same time, studies indicate that a low socioeconomic level and lack of education are directly connected to risky sexual behaviors, sustaining the idea of increase in the incidence of STDs for the impoverished and requiring specific interventions and studies for this group (Taquette, Vilhena, & De Paula, 2004;Waystaff, Delameth, & Havens, 1999). Whitehead (2001) relate that upon analyzing a proabstinence religious program, despite finding a greater rate of abstinent youth in the religious group, they also found that these same youths used fewer condoms and contraceptive methods in their first sexual encounters.…”
mentioning
confidence: 99%
“…Such aspects are related to healthy behaviors, including sexual behaviors and protection. At the same time, studies indicate that a low socioeconomic level and lack of education are directly connected to risky sexual behaviors, sustaining the idea of increase in the incidence of STDs for the impoverished and requiring specific interventions and studies for this group (Taquette, Vilhena, & De Paula, 2004;Waystaff, Delameth, & Havens, 1999). Whitehead (2001) relate that upon analyzing a proabstinence religious program, despite finding a greater rate of abstinent youth in the religious group, they also found that these same youths used fewer condoms and contraceptive methods in their first sexual encounters.…”
mentioning
confidence: 99%
“…As a rule, younger adolescents (aged 10 to 14) still have incipient abstract thought capabilities, which makes them more vulnerable to risk exposure without regard for the consequences. The greater vulnerability of younger girls has been described in prior studies reporting a significant association between young age at onset of sexual activity and variables such as coming from a poor background and being exposed to physical or sexual abuse, among other factors 2 . Other elements also contribute to increased risk among adolescent girls, including biological and psychosocial immaturity, financial dependence, non-awareness of the legitimacy of sexual freedom, gender violence [6][7][8][9] and drug and alcohol consumption 10,11 .…”
Section: Introductionmentioning
confidence: 81%
“…According to some studies conducted in Brazil, the onset of sexual activity in adolescents has occurred at increasingly early ages 1,2,3 . Mean age at first genital intercourse among females is currently less than 15 years 4 .…”
Section: Introductionmentioning
confidence: 99%
“…No estudo realizado entre universitários de uma universidade pública paulista (7) , as idades foram 17 anos no grupo formado pelos homens e 18 anos no das mulheres. Diferentemente, em estudo realizado com 356 adolescentes que freqüentavam um ambulatório de Saúde do Adolescente da Universidade Estadual do Rio de Janeiro, a idade da primeira relação sexual se concentrou na faixa dos 14-15 anos (18) . Este início precoce talvez seja explicado pela diferença de perfil destes adolescentes daqueles que são universitários: quase metade deles era portadora de DSTs e apresentava atraso escolar maior que dois anos.…”
Section: Discussão Discussão Discussão Discussão Discussãounclassified
“…Além disso, foram encontrados baixos índices de uso de preservativo na faixa etária de 15 a 19 anos entre adolescentes do Rio de Janeiro que freqüentavam um ambulatório de Saúde do Adolescente (18) . Em contraste com esse dado, um inquérito nacional (19) realizado com 6000 indivíduos de 15 a 54 anos evidenciou que os mais jovens (15 a 24 anos) foram os que mais usaram o preservativo.…”
Section: Discussão Discussão Discussão Discussão Discussãounclassified